The role of sociodemographic, psychosocial, and behavioral factors in the use of preventive healthcare services in children and adolescents: results of the KiGGS Wave 2 study - Bammert, Philip; Schüttig, Wiebke; Iashchenko, Iryna; Spallek, Jacob; Rattay, Petra; Schneider, Sven; Richter, Matthias; Pischke, Claudia R.; Dragano, Nico; Sundmacher, Leonie (BMC pediatrics, 2024)
Background: In Germany, various preventive services are offered to children and adolescents. These include regular standardized examinations (so called U/J examinations) and several vaccinations. Although strongly recommended, most of them are not mandatory. Our aim is to identify factors associated with the use of U/J examinations and vaccination against diphtheria, hepatitis B, Hib, pertussis, polio, and tetanus. While previous research has focused on sociodemographic factors, we also include socioeconomic, behavioral, and psychosocial factors. Methods: We analyzed cross-sectional data from 15,023 participants (aged 0–17 years) of the nationwide representative KiGGS Wave 2 Survey. Participation in U/J examinations was assessed using a questionnaire, filled out by participants and/or their parents. Information on vaccination status was drawn from the participants’ vaccination booklets. To identify relevant determinants for the use of preventive examinations and vaccinations, unadjusted and adjusted logistic regression models were employed with up to 16 different independent variables. Results: Various independent variables showed an association with the use of preventive services. Higher socioeconomic status, absence of migration background, and lower household size were associated with significantly higher utilization of U examinations. Parents’ marital status, area of residence, behavioral and psychosocial factors yielded insignificant results for most U/J examinations. Higher vaccination rates were found for children with no migration background, with residence in eastern Germany, lower household size, and with married parents. Conclusion: This study attempted to depict the influence of sociodemographic, psychosocial, and behavioral factors on the use of several preventive services. Our results indicate that predominantly sociodemographic variables influence the use of preventive services. Further efforts should be made to investigate the interplay of different determinants of healthcare use in children and adolescents.